P298 Budesonide MMX versus Prednisolone for Ulcerative Colitis: Comparative outcomes from a British retrospective multi-centre study. (27th May 2021) - Rosiou, K; Ong Ming San, E; Kumar, A; Esquivel, K; Almas, S; Stokes, D; Ng, T; Jayasooriya, N; Ranasinghe, I; Pollok, R; Brookes, M; Selinger, C P
Abstract: Background: Budesonide MMX (Cortiment) is superior to placebo for mild to moderate UC flares and has a favourable side effect profile. However, no head-to-head data with Prednisolone exist. During the COVID-19 pandemic many IBD units chose Cortiment as first line treatment for outpatients' flares of UC. The aim of this retrospective study was to compare outcomes of Cortiment vs Prednisolone treatment for UC. Methods: Hospital based prescriptions from of 3 UK IBD units were extracted from computerized pharmacy records for the time periods between 1/3/2019 – 30/6/2019 and 1/3/2020 – 30/6/2020. All adult outpatients treated with oral steroids for a flare of UC were included. Baseline data included age, sex, phenotype, IBD medications, symptoms and changes to medication at time of steroid prescription. Follow up data included need for hospital admission for acute severe ulcerative colitis, symptoms at 4 weeks and end of treatment, need for rescue Prednisolone (Cortiment group only). Primary outcome was symptomatic improvement at 4 weeks. Results: The 2019 (94 patients) and 2020 (127 patients) cohorts did not differ significantly with regards to age, sex, phenotype and baseline characteristics. The proportion of Cortiment prescriptions rose significantly from 24.5% in 2019 to 70.1% in 2020 (p<0.001). At week 4 of treatment there were statistically significant differences in mean bowel frequency (3.49 in 2019 vs 5.85 in 2020, p=0.001), rectal bleeding <50% (89.7% of patients in 2019 vs 73.1% in 2020, p=0.039) and physician global assessment (39.2% of patients in remission in 2019 compared to 19.8% in 2020, p=0.045).There was no significant difference in hospital admissions, rectal bleeding and physician global assessment at end of treatment. Patients prescribed Cortiment in 2019 had similar baseline characteristics to those prescribed Cortiment in 2020. Mean bowel frequency at four weeks was significantly higher in 2020 (6.18) compared to 2019 (3.69, p=0.034), but rectal bleeding (p=0.388) and physician global assessment at week four did not differ between 2019 and 2020 (p=0.422). Rescue Prednisolone was required in 10% of Cortiment patients in 2019 vs 31.3% in 2020 (p=0.058). Conclusion: Cortiment was used as the main first line steroid for UC during the pandemic to reduce the risk of adverse COVID-19 outcomes. This change in treatment was, however, associated with worse UC outcomes at 4 weeks and 31% needed rescue Prednisolone. As active IBD is associated with worse COVID-19 outcomes clinicians should carefully evaluate the choice of steroid to achieve optimal disease control and COVID-19 risk minimization.